2017
DOI: 10.1073/pnas.1618714114
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in cellular metabolism triggered by URA7 or GLN3 inactivation cause imbalanced dNTP pools and increased mutagenesis

Abstract: Eukaryotic DNA replication fidelity relies on the concerted action of DNA polymerase nucleotide selectivity, proofreading activity, and DNA mismatch repair (MMR). Nucleotide selectivity and proofreading are affected by the balance and concentration of deoxyribonucleotide (dNTP) pools, which are strictly regulated by ribonucleotide reductase (RNR). Mutations preventing DNA polymerase proofreading activity or MMR function cause mutator phenotypes and consequently increased cancer susceptibility. To identify gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 102 publications
3
32
0
Order By: Relevance
“…Haploid yeast deficient in Polδ proofreading require functional MMR for survival (26). Recent work has demonstrated that polymerase fidelity and MMR can compensate for defects in cellular metabolism that lead to dNTP pool imbalances and help maintain a normal low mutation rate despite the abnormal dNTP levels (60,61). Extrinsic proofreading of Pole errors by Polδ shown here as well as proofreading of Polα errors by Polδ shown previously (9) is yet another mechanism of redundancy to prevent accumulation of DNA replication errors.…”
Section: Genome Stability Requires Redundancy Of Replication Fidelitymentioning
confidence: 53%
“…Haploid yeast deficient in Polδ proofreading require functional MMR for survival (26). Recent work has demonstrated that polymerase fidelity and MMR can compensate for defects in cellular metabolism that lead to dNTP pool imbalances and help maintain a normal low mutation rate despite the abnormal dNTP levels (60,61). Extrinsic proofreading of Pole errors by Polδ shown here as well as proofreading of Polα errors by Polδ shown previously (9) is yet another mechanism of redundancy to prevent accumulation of DNA replication errors.…”
Section: Genome Stability Requires Redundancy Of Replication Fidelitymentioning
confidence: 53%
“…dNTP pools are tightly controlled and an imbalance of dNTPs is observed in a variety of disease conditions such as cancer and mitochondrial diseases[1,2]. Both imbalanced dNTP pools as well as irregularly large amounts of all dNTPs have been shown to be associated with increased errors in nucleotide selectivity combined with inefficient proofreading during DNA replication and eventual oncogenesis, likely attributed to this buildup of mutations[3,4]. During the cell cycle, dNTP pools are augmented for DNA synthesis and are generally elevated during proliferation [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in genes encoding MMR proteins and DNA polymerase proofreading activities are linked to elevated mutation rates and diseases such as cancer, and these rates are synergistically increased in double mutants (2,3). In PNAS, Schmidt et al (4) describe work in which they screened for defects in genome stability in genetic backgrounds where processes that limit mutagenesis were compromised. Their work provides new insights for how cellular metabolism and nucleotide pool homeostasis interact to avoid mutation and maintain genome stability.…”
mentioning
confidence: 99%
“…Previous screens of this type, performed in functional DNA polymerase backgrounds, identified genome stability factors that are likely to be important targets in cancer (5-7). Schmidt et al (4) used this approach to identify new targets whose effects on mutation rate are normally buffered by the fidelity of DNA polymerases. Their approach identified knockout mutations in the EXO1, RRM3, GLN3, URA7, and SHM2 genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation